2017
DOI: 10.1111/ejh.12912
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Plasminogen Activator Inhibitor‐1 (PAI‐1) 4G/5G promoter polymorphism in Indian venous thrombosis patients: A case‐control study

Abstract: PAI-1 4G/4G is a strong risk factor for venous thrombosis in Indian patients and should be included in laboratory testing panel of thrombophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…Reported data about the prevalence of this homozygous mutation are controversial. Based on several study, the PAI-1 4G/4G might be a risk factor, even more if is associated with other defects such as hyperhomocysteinemia, protein C or S deficiency or factor VIII hyperactivity -this also being present in our case (14). Regarding the MTHFR A1298C mutation, there was no study that could demonstrate the association with the thrombosis risk (13).…”
Section: Discussionmentioning
confidence: 75%
“…Reported data about the prevalence of this homozygous mutation are controversial. Based on several study, the PAI-1 4G/4G might be a risk factor, even more if is associated with other defects such as hyperhomocysteinemia, protein C or S deficiency or factor VIII hyperactivity -this also being present in our case (14). Regarding the MTHFR A1298C mutation, there was no study that could demonstrate the association with the thrombosis risk (13).…”
Section: Discussionmentioning
confidence: 75%
“…A prospective large nationwide cohort study with sufficient number of patients with both MVT and systemic VTE is needed to evaluate differences in risk factor profiles of other thrombophilias than factor V Leiden and prothrombin mutation. Novel candidate markers for venous thrombosis such as plasminogen activator inhibitor-1 should then be considered in the test panel [ 18 , 19 ]. Since thrombophilia profiles may vary greatly in different populations [ 7 , 20 ], the fact that the compared cohorts are from the same population constitutes an important strength of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…DVT is a common disease caused by genetic factors and a variety of external factors, and the genetic factors are more significant in DVT [5][6][7]. There are several risk factors in the process of the formation of DVT [8,9]. In recent years, some studies have confirmed that coagulation factor VG1691A gene polymorphism (FV Leien mutation), the polymorphism of prothrombin gene G20210A and the polymorphism of MTHFR gene C677T are closely related to white and Indian DVT [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%